2013
DOI: 10.1016/j.cell.2013.06.044
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Mediated Modular RNA-Guided Regulation of Transcription in Eukaryotes

Abstract: SUMMARY The genetic interrogation and reprogramming of cells requires methods for robust and precise targeting of genes for expression or repression. The CRISPR-associated catalytically inactive dCas9 protein offers a general platform for RNA-guided DNA targeting. Here we show that fusion of dCas9 to effector domains with distinct regulatory functions enables stable and efficient transcriptional repression or activation in human and yeast cells with the site of delivey determined solely by a co-expressed short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
2,823
2
17

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 3,218 publications
(2,978 citation statements)
references
References 46 publications
41
2,823
2
17
Order By: Relevance
“…Furthermore, in CAL51 cells, a breast cancer cell line heterozygous for the risk SNPs, allele-specific 3C showed that only the protective allele participated in chromatin looping, suggesting that the risk allele abrogates looping between PRE1 and the CUPID1 and CUPID2 promoter ( Figures 1E and S4C). We also silenced PRE1 by targeting a nuclease-inactive dCas9 fused to the Krüppel-associated box (KRAB) repressor (dCas9-KRAB) 27 to the PRE1 enhancer and confirmed that CUPID1, CUPID2, and CCND1 levels were significantly reduced ( Figure 1F). …”
Section: Results Lncrnas Expressed From the 11q13 Breast Cancer Riskmentioning
confidence: 60%
“…Furthermore, in CAL51 cells, a breast cancer cell line heterozygous for the risk SNPs, allele-specific 3C showed that only the protective allele participated in chromatin looping, suggesting that the risk allele abrogates looping between PRE1 and the CUPID1 and CUPID2 promoter ( Figures 1E and S4C). We also silenced PRE1 by targeting a nuclease-inactive dCas9 fused to the Krüppel-associated box (KRAB) repressor (dCas9-KRAB) 27 to the PRE1 enhancer and confirmed that CUPID1, CUPID2, and CCND1 levels were significantly reduced ( Figure 1F). …”
Section: Results Lncrnas Expressed From the 11q13 Breast Cancer Riskmentioning
confidence: 60%
“…dCas9 itself has a repressive effect on gene expression because of steric hindrance of the transcription initiation components. Chromatin modifying repressor domains have been fused to dCas9 to improve the repression effect 60. Additionally, scaffold RNAs fused to an RNA aptamer can be used to recruit activator or repressor effectors 61.…”
Section: Crispr/cas9mentioning
confidence: 99%
“…Complete disruption of the endonuclease activities (RuvC D10A along with HNH H840A ) results in a catalytically inactive Cas9, or dead-Cas9 (dCas9) [78,79]. This has been exploited to physically block the transcriptional machinery when targeted in the promoter region of a gene of interest, coined CRISPR interference (CRISPRi) [22,34] (Fig. 1c).…”
Section: Expanding Cas9 Features Through Enzyme Engineeringmentioning
confidence: 99%